Envisioning the Future of Learning for Creativity, Innovation and Entrepreneurship - Papageorgiou, Kyriaki (De Gruyter, 2022)
How can educators, teachers and trainers stay current and address the dynamic opportunities of creativity, innovation and entrepreneurship teaching and training? This book offers an overview of the VISION research project, which provides an understanding of the future of education in these areas and describes the approach taken by the VISION team, including the findings of interviews with more than 130 global stakeholders.